Programa Novo Mais Educação: um estudo de caso em duas escolas de educação básica de Oeiras do Pará - SOUZA, Kenanny Semayas Palheta de (2022)
The present study seeks to analyze the implementation of the Novo Mais Program in two schools of the municipal school network. It is a central problem to understand how the Program is practiced, being 2018, the first year of effective operation in the schools of the city of Oeiras do Pará, in what way it seeks better results in Portuguese and mathematics, through pedagogical accompaniment in these schools. areas, also offering activities in the areas of art and culture, sports and laser, extending the student's stay in school, reading official documents, observations during the execution of the Program activities, and interviews with professionals, students and community of the Program in order to know its operation and execution. It was necessary to draw a line with the Program Predecessor More Education Program understanding that the programs differ in their objectives and purposes, but both bring with them the search for better educational results in the expansion of the school day. The More Education Program characterized by offering activities of a formative nature to the students being a strategy for the implementation of integral education, however the program did not have significant results in the city with a worn image on itself. Reformulated and "renamed" to Programa Novo Mais Educação, the Program aims to improve Portuguese Language and Mathematics learning in order to improve the low numbers presented by the Basic Education Development Index (IDEB), but which has brought a new perspective to its execution and to the work in schools that have joined, expecting positive results for schools and students. The program brings the increase of the school day to some students, and ends up being seen as a way of implementing integral education, which according to some actors, a possible reality, but not for our reality in the face of the structural difficulties faced by schools. It was verified that even the Program came to the benefit of the student, there is still resistance from students and parents, due to the students having to come in two shifts to school, this causes a large number of students lacking in the activities being there must always be a more intense interaction with the school and family. Difficulties in the organization of school boards also reflected in the implementation of the program, with delays in the beginning of activities and delay in the payment of suppliers and employees, making it difficult to access materials that provide a basic structure for carrying out the Program activities. It has been seen that it is necessary not only the program is present in the school, it has to be part of the school and the school part of it, so that the results can reflect positively.